Groundwater resources investigation using geophysical method in crystalline basement and volcanic rock regions of countries belonging to the East African Rift Valley: A review - Khan, Musabbir Ahmed; Nakayama, Hiroyuki; Nakaya, Shinji (Journal of African earth sciences (1994), 2024)
The East African Rift Valley (EARV) is characterized by diverse geology, including crystalline, volcanic, and metamorphic rocks, shaped by tectonic activity leading to complex faulting and fractured zones. These fractured zones in hard rock serve as crucial groundwater reservoirs, often explored using electric resistivity methods. Countries surrounding the EARV, such as Burundi, Djibouti, the DR Congo, Eritrea, Ethiopia, Kenya, Malawi, Mozambique, Rwanda, Tanzania, Uganda, and Zambia, share similar geological features linked to the rift system. Groundwater investigation in these regions, particularly using geo-electric resistivity methods, is essential for understanding subsurface geology, potential aquifers, and structural features, additionally, water quality, and dominant water sources of these countries are reviewed to categorize twelve countries based on the availability of the groundwater investigations and country status. The review results highlight some countries rely on weathered and fractured basement aquifers concentrated in specific areas, while others utilize aquifers associated with various geological settings and surface water as alternative sources due to the limited yield from basement complex aquifers. Therefore, 12 countries were classified broadly into three types, and a resistivity distribution map was created to visually show the present status of research and development works of the existence of gaps and limitations, which is generally in line with this comprehensive review. The outcomes of this study are useful for future research and sustainable development by informing the resistivity distribution trend and water resource usage in each country, as a result, expecting to contribute to the effective utilization of groundwater resources in the challenging crystalline basement and volcanic rock environments of the region. •This review targeted 12 countries around the East African Rift Valley.•The review reveals a visual research gap for groundwater in hard rocks.•Kenya, the DR Congo, and Zambia mainly use non-hard rock aquifers.•Tanzania and Ethiopia threaten safe drinking water by geogenic contaminations.•Other seven countries rely on hard rock aquifers, yet less explored.